PENGARUH KEPRIBADIAN TERHADAP PERILAKU PENGGUNAAN ONLINE TRADING DAN PREFERENSI RESIKO PADA INVESTOR - Siregar, Hasnah Sabrina; Ermawati, Wita Juwita; Fariyanti, Anna (Jurnal Aplikasi Bisnis dan Manajemen, 2021)
One way to obtain information is through online trading, which also serves as a place for transacting. Personality is a factor that affects how a person behaves and makes decisions, including behavioral finance. This research aimed to analyze the effect of investors’ personality on online trading use behavior and investors’ risk preference. The data were obtained from online questionnaires distributed through social media with a total of 240 respondents. This research used a structural equation modeling (SEM) to measure the relationship between latent variables, namely the five personality variables of the International Personality Pool Item-Big Five Model (IPIP-BFM), investors’ risk preference, and online trading behavior. The data were processed using SPSS and SEM-PLS. The result indicated that openness to experience positively and significantly affected online trading use behavior and investors’ risk preference. Conscientiousness, extraversion, agreeableness, and neuroticism insignificantly affected online trading use behavior and investors’ risk preference. The behavior of using online trading had a positive and significant effect on risk preference. The result showed that if investors were more open to something, they would use online trading more intensely and become more risk-seeker. Keywords: behavioral finance, online trading, personality, risk preference, SEM-PLS